Distribusi Mutasi Asp614Gly pada Spike Protein SARS-CoV-2 di Sumatera Barat - Andani Eka Putra; Dessy Arisanty; Dede Rahman Agustian (Faculty of Medicine, Universitas Andalas, 2024)
Objective: This study aims to map the distribution of the Aspartate 614 to Glycine (Asp614Gly) mutation in the spike protein of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) circulating in West Sumatra, to understand the extent of its spread within the local population. Methods: RNA samples were taken from 98 confirmed COVID-19 cases across various area in West Sumatra. Genetic amplification and next-generation sequencing (NGS) were performed to identify the presence of the Asp614Gly mutation. The frequency of mutations was analyzed using bioinformatics software. Results: Out of the 98 samples analyzed, approximately 97% exhibited the Asp614Gly mutation. The geographic distribution of this mutation showed significant variation among the districts of West Sumatra, with the highest prevalence in urban areas. Conclusion: These findings indicate that the Asp614Gly mutation is highly prevalent in West Sumatra. Associated with increased virus transmissibility, this mutation dominates the circulating virus strains in the region, highlighting the need for ongoing genetic surveillance to guide public health interventions and vaccination strategies.